Comparative outcome analysis of osseointegrated reconstruction and replantation for digital amputations. (May 2022) - Li, Andrew T.; Shepherd, Angela; Gray, Steven J.; Slattery, Philip; Bruscino-Raiola, Frank
The long-term outcomes of osseointegration for digital amputations are not well established, and it is not known whether osseointegration can achieve similar function and patient satisfaction to conventional surgical options such as replantation and microsurgical toe transfer. We compared the long-term outcomes after digital osseointegration and replantation. Six patients treated by osseointegration and seven patients treated by replantation were included, with median follow-ups of 8 years and 4.6 years, respectively. Outcomes were assessed using the Michigan Hand Outcomes Questionnaire, grip and pinch strength, range of motion, two-point discrimination, Semmes-Weinstein tests, Jebsen-Taylor Hand Function Test and clinical photography. Osseointegration was associated with poorer sensibility and range of motion than replantation; no other differences reached statistical significance. Long-term osseointegration is a safe and effective reconstructive option that can deliver excellent outcomes in appropriately selected patients. Level of evidence: IV